Epidural steroid for low back pain in pain management clinic - Pradhan, B; Marhatta, MN; Amatya, R (Journal of Institute of Medicine Nepal, 2009)
Background: Epidural steroid injection for chronic low back pain is the most common procedure performed in the pain management clinics. This study was conducted to evaluate the efficacy of epidural steroid injection for various causes of low back pain in the patients attending pain management clinic (PMC) of this institute. Methods: This is a prospective observational study of the patients attending in pain management clinic with the complaints of low back pain in the year 2007. All the patients who were treated with the epidural steroid injections were enrolled in the study. Data regarding the age of the patients, frequency of steroid injections, outcome of the procedure and complications if any were noted. Results: Majority of the patients attending the PMC complained of low back pain. (Table 1) Among them 74% of the patients had prolapsed intervertebral disc. Among these, 97 patients received epidural steroid injections, among which 34 (35%) patients received single dose only whereas 38 (39%) and 25 (26%) patients received second and third dose of steroid. Among the patients who received epidural steroid, 50 (51%) had significant relief of the symptoms and signs, whereas 18 (19%) patients had moderate relief, 8 (8%) patients had no relief and follow up (FU) was lost in 22 patients (22%). Conclusion: It is concluded that the interlaminar epidural steroid injection for lumbar radicular pain is an effective method of treatment. Key Words: Low back pain, epidural, steroid, interlaminar Journal of Institute of Medicine, August, 2008; 30:2 2-5 The full text of this paper is available from the Journal of Institute of Medicine website